Character Education through the Main Jaran Tradition: Child Jockeys' Role in Sustainable Cultural Tourism and Youth Empowerment in Sumbawa - Supriadi, Supriadi; Khadafie, Muammar (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This ethnographic study investigates the dual role of the Main Jaran (traditional horse racing) tradition in Sumbawa, Indonesia, as both a medium for character education and a cultural tourism asset. The study aims to Examine how Main Jaran fosters character development in child jockeys (ages 7–15) through its training and rituals. Assess its potential as a cultural tourism attraction, considering both opportunities and challenges. Propose an integrative model for sustainable development that balances cultural preservation, youth empowerment, and ethical tourism. Method: The study employs in-depth interviews and field observations with 12 child jockeys, their families, community leaders, and cultural experts. Additionally, survey data from 150 were targeted and 77 were usable fromdomestic and international touristswere analyzed to evaluate Main Jaran’s tourism appeal. This survey also provided a quantitative validation of the qualitative findings. A SWOT analysis was conducted to identify strengths, weaknesses, opportunities, and threats. Results: Main Jaran serves as a formative social space, instilling discipline, responsibility, courage, cooperation, and cultural pride in young jockeys. Training routines emphasize physical endurance, strict schedules, and empathy for horses, embedding values through lived experience. 78% of surveyed tourists (n=77) expressed interest in Main Jaran due to its uniqueness and educational value. The tradition symbolizes local wisdom, historically linked to agricultural rituals, and acts as a vehicle for intergenerational value transmission. Concerns include child safety risks and the ethical implications of commercialization, necessitating community-based regulation and safeguards. Novelty: This study introduces an integrative model that synergizes character education, sustainable cultural tourism, and child protection. It highlights Main Jaran as a dynamic intersection of tradition, identity, and innovation, offering a blueprint for heritage preservation, youth development, and local economic empowerment. The findings underscore the potential of community-based traditions to serve dual purposes educating youth while attracting ethical tourism—when developed with cultural sensitivity and ethical oversight.